2017
DOI: 10.7717/peerj.3087
|View full text |Cite
|
Sign up to set email alerts
|

Computer modelling reveals new conformers of the ATP binding loop of Na+/K+-ATPase involved in the transphosphorylation process of the sodium pump

Abstract: Hydrolysis of ATP by Na+/K+-ATPase, a P-Type ATPase, catalyzing active Na+ and K+ transport through cellular membranes leads transiently to a phosphorylation of its catalytical α-subunit. Surprisingly, three-dimensional molecular structure analysis of P-type ATPases reveals that binding of ATP to the N-domain connected by a hinge to the P-domain is much too far away from the Asp369 to allow the transfer of ATP’s terminal phosphate to its aspartyl-phosphorylation site. In order to get information for how the tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
1
2
0
Order By: Relevance
“…Moreover, it was also found that the NKA catalytic cycle is affected by Mg 2+ ions in the way that in the E 1 state, the Mg 2+ ions induce the cavity occlusion, followed by autophosphorylation and transition to the E 2 state [ 77 ]. These data are further confirmed by the computational simulations by [ 78 ], who used molecular docking and simulations of molecular dynamics to show that Mg 2+ facilitates NKA transition from the open to occluded conformation and subsequent autophosphorylation.…”
Section: Catalytic Cycle Of Na + /K + -Atpasesupporting
confidence: 59%
“…Moreover, it was also found that the NKA catalytic cycle is affected by Mg 2+ ions in the way that in the E 1 state, the Mg 2+ ions induce the cavity occlusion, followed by autophosphorylation and transition to the E 2 state [ 77 ]. These data are further confirmed by the computational simulations by [ 78 ], who used molecular docking and simulations of molecular dynamics to show that Mg 2+ facilitates NKA transition from the open to occluded conformation and subsequent autophosphorylation.…”
Section: Catalytic Cycle Of Na + /K + -Atpasesupporting
confidence: 59%
“…In P-ATPases, ATP binding induces conformational changes in the N-domain structure [20,24,75,76], that may also be observed in the isolated N-domain [20,23,28,29]. In this study, ATP binding quenched the intrinsic uorescence of the NKA N-domain (Fig.…”
Section: Cation Interaction Mediated Nka N-domain Intrinsic Uorescenc...mentioning
confidence: 50%
“…The most similarity region among α isoforms is related to transmembrane hydrophobic regions, the cytoplasmic mid-region around the phosphorylation site (Asp369), and the C-terminus [7]. Numerous studies have been done to identify conserved motifs and amino acids in similar or different regions and their role in ion transport mechanism and other properties of the enzyme obtained during evolution [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%